2015
DOI: 10.1002/hed.24147
|View full text |Cite
|
Sign up to set email alerts
|

Health care–associated infections in patients with head and neck cancer treated with chemotherapy and/or radiotherapy

Abstract: Health care-associated infections increased over time, with corresponding increases in gram-negative pathogens and resistant strains. Prevention and treatment protocols should be implemented in institutions treating patients with head and neck cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1009-E1013, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Recent studies have demonstrated that multidrugresistant Gram-negative bacteria have been a growing concern for patients in ICUs due to their significant ef-fect on patient mortality (20)(21)(22). In a multicenter pointprevalence study conducted in Turkey, researchers reported that Gram-negative bacteria constituted nearly 75% of all ICU pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that multidrugresistant Gram-negative bacteria have been a growing concern for patients in ICUs due to their significant ef-fect on patient mortality (20)(21)(22). In a multicenter pointprevalence study conducted in Turkey, researchers reported that Gram-negative bacteria constituted nearly 75% of all ICU pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Risks of viral and bacterial pneumonia are increased among HNSCC patients receiving chemotherapy and/or radiotherapy given the presence of unique risk factors (eg, depressed immune function, older age, malnutrition, smoking and alcohol abuse, tumor location, and comorbidities) 8,26,32,34,57 . Pulmonary viral infections frequently occur in patients with impaired cellular immunity, with cytomegalovirus and herpes group viruses being common sources 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In a review of healthcare‐associated infections in HNSCC patients treated with chemotherapy and/or RT, respiratory tract infections were most common 34 . Pseudomonas aeruginosa represented the majority of gram‐negative organisms (49%) compared to gram‐positive pathogens (35%), where Staphylococcus aureus predominated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…depressed immune function, older age, malnutrition, smoking and alcohol abuse, tumor location, and comorbidities). 8,26,[54][55][56] Pulmonary viral infections frequently occur in patients with impaired cellular immunity, with cytomegalovirus and herpes group viruses being common sources. 11 Influenza, parainfluenza, respiratory syncytial virus, rhinovirus, and adenovirus, are also recognized as frequent pulmonary pathogens, particularly among immunocompromised cancer patients with respiratory illness.…”
Section: Viral and Bacterial Pneumonia In Hnsccmentioning
confidence: 99%